Malignant transformation of gastric hyperplastic polyps in an autoimmune gastritis patient—a case report and literature review - Wang, Yingqi; Liu, Zijin; Gao, Wei; Jia, Tianxu; Hong, Jiayi; Cai, Ling; She, Jing; Zhai, Huihong (Frontiers in Medicine, 2025)
The cancer risk in autoimmune gastritis (AIG) remains controversial. Malignant transformation of gastric hyperplastic polyps (GHPs) in an AIG patient is rare. The esophagogastroduodenoscopy (EGD) of a 75-year-old male patient showed a 0.8 cm GHP. Endoscopic resection was conducted, and the pathological findings showed high-grade dysplasia and intramucosal moderately differentiated adenocarcinoma. Follow-up at 1 year confirmed no sign of recurrence. 18 months post-operatively, another EGD confirmed advanced-stage AIG, evidenced by characteristic endoscopic/histologic findings, positive anti-parietal cell antibody, low pepsinogen I/II ratio, significantly elevated gastrin-17, low vitamin B12, and negative Helicobacter pylori (Hp) serology. Concurrent Hashimoto's thyroiditis and vitiligo were also noted. We here report a rare case of early malignant transformation of a small GHP arising in a context of AIG. Elevated gastrin levels may be a potential risk factor for cancer development in Hp-negative AIG. Endoscopic resection can be considered for early-stage cancerous transformation of GHPs.